Deducing the Role of Virus Genome-Derived PIWI-Associated RNAs in the Mosquito–Arbovirus Arms Race - Blair, Carol D. (Frontiers in Genetics, 2019)
The PIWI-associated RNA (piRNA) pathway is known for its role in protection of genome integrity in the germline of Drosophila melanogaster by silencing transposable elements. The piRNAs that target transposons originate in piRNA clusters in transposon-rich regions of the Drosophila genome. In Aedes aegypti and Ae. albopictus mosquitoes, which are among the most important vectors of arthropod-borne viruses (arboviruses), the number of PIWI-family genes has expanded and some are expressed in somatic, as well as germline, tissues. These discoveries have led to extensive research to explore the possible expanded functional roles of the piRNA pathway in vector mosquitoes. Virus genome-derived piRNAs (vpiRNAs) have been demonstrated in Aedes spp. cultured cells and mosquitoes after infection by arthropod-borne alpha-, bunya-, and flaviviruses. Generation of cDNA fragments from RNA genomes of alpha-, bunya-, and flaviviruses (vDNAs) has been demonstrated in cultured Aedes spp. cells; and endogenous viral elements (EVEs), cDNA fragments of non-retroviral RNA virus genomes, are found more abundantly in genomes of Ae aegypti and Ae albopictus than other vector mosquitoes. These observations have led to speculation that vDNAs are integrated into vector genomes and serve as templates for transcription of antiviral vpiRNA precursors. However, no EVEs derived from alphavirus genomes have been demonstrated in genomes of any vector mosquito. In addition, although EVEs have been shown to be the source of piRNAs, the preponderance of EVEs described in Aedes spp. vectors are derived from the genomes of insect-specific viruses rather than acutely-infecting arboviruses. Furthermore, the signature patterns of the “ping-pong” amplification cycle that maintains transposon-targeting piRNAs in Drosophila are also evident in alphavirus genome-derived vpiRNAs, but not in flavivirus genome-derived piRNAs. These divergent observations have rendered deciphering the mechanism(s) of biogenesis and potential role of vpiRNAs in the mosquito-arbovirus arms race difficult, and will be further discussed here.